Problematika Implementasi Proyek Penguatan Profil Pelajar Pancasila Pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti - Fauza, Rahmatul; Pebrina, Rizki; Trisoni, Ridwal; Maimori, Romi (SURAU : Journal of Islamic Education, 2024)
This research aims to analyze teachers' difficulties in implementing P5 in junior high schools. The P5 program is implemented in stages and requires quite a long time including planning, implementation and evaluation. This research uses a qualitative descriptive approach. The main instrument is the researcher himself. PAI teachers do not understand the concept of an independent curriculum and lack training in compiling teaching modules, teachers are less able to determine suitable methods for teaching. Limited facilities and classrooms, lack of textbooks, teachers are focused on written and oral assessments only, implementation of assessments is limited, teachers have not used special applications in learning because they mostly rely on manuals. Problems in the planning aspect are that PABP teachers do not understand the concept of an independent curriculum, lack training in compiling teaching modules, and are less able to determine teaching methods. Teachers' problems in the implementation aspect are difficulty in managing P5 time, lack of varying methods, students do not yet reflect Pancasila values. The problem in the evaluation aspect is that the teacher has not used a special application, the difficulty in reviewing the assessment results takes time Abstrak Penelitian ini bertujuan untuk menganalisis kesulitan guru dalam menerapak P5 di SMP. Program P5 tersebut dilaksanakan secara bertahap dan membutuhkan waktu yang cukup lama termasuk perencanaan, pelaksanaan dan evaluasi. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Instrument utamanya adalah peneliti sendiri. Guru PAI kurang memahami konsep kurikulum merdeka dan kurangnya pelatihan dalam menyusun modul ajar, guru kurang mampu menentukan metode yang cocok dalam mengajar. Keterbatasan fasilitas dan ruang kelas, kekurangan buku paket, guru terfokus kepada asesmen tertulis dan lisan saja, pelaksanaan asesmen terbatas, guru belum menggunakan aplikasi khusus dalam pembelajaran karena lebih banyak ke manual saja. Problematika dalam aspek perencanaan yaitu guru PABP kurang memahami konsep kurikulum merdeka, kurang pelatihan dalam menyusun modul ajar, kurang mampu menentukan metode dalam mengajar. Problematika guru dalam aspek pelakasanaan yaitu kesulitan untuk mengatur waktu P5, kurang memvariasikan metode, peserta didik belum mencerminkan nilai pancasila. Problematika dalam aspek evaluasi yaitu guru belum menggunakan aplikasi khusus, kesulitan dalam menelaah hasil assessmen butuh waktu.